Diagnosis of Right Ventricular Cardiac Insufficiency in the Acute Bronchial Asthma in Children - V.А. Kondratiev; А.V. Reznik (Zaslavsky O.Yu., 2016)
With the aim to define the informative clinical-echocardiographic diagnostic signs for the development of right ventricular cardiac insufficiency in children in the acute bronchial asthma, 64 patients aged 5 to 17 years were examined. During investigations of pathologic changes in the cardiovascular system followed by mathematic processing of diagnostic symptoms using sequential analysis by Wald, there has been shown a high informative significance of a number of signs for the diagnosis of right ventricular cardiac insufficiency in children in the acute bronchial asthma, namely: elevation of systolic pressure in the pulmonary artery, enlargement of the echocardiographic sizes of right ventricular and right atrial cavities, isovolumic relaxation time of the right ventricle; tachycardia or bradycardia, hyperkinetic type of hemodynamics, disorders of ventricular repolarization according to electrocardiography data. Presence of the informative diagnostic signs of right ventricular cardiac insufficiency in a sick child in the acute bronchial asthma enables to diagnose this complication with the probability of 90 % and more and to carry out appropriate correction of the therapy.